The Periodic Boundary Problem and the Initial Value Problem for a Nonlinear System of Equations of Changing Type (Journal of Partial Differential Equations, 2020)
In this paper, we study the global existences of regular solutions, classical solutions and C^&#8734-solutions of the periodic boundary problem and the initial value problem for a nonlinear system of equations of changing type.
Keywords: Changing type; regular solutions; classical solutions; C^&#8734-solutions; the periodic boundary problem; the initial value problem